A sputtering deposited insulating coating and a preparation method thereof
Through electrochemical polishing and sputtering deposition of Cr-Ce alloy coating and Cr-Si-C insulating coating, the problem of poor bonding between the insulating coating and the metal substrate is solved, good bonding strength and insulating performance are achieved, and the service life is extended.
Patent Information
- Application Number
- CN202511080785.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2045-08-04
AI Technical Summary
In the prior art, when an insulating coating is prepared by magnetron sputtering, the bonding strength between the insulating coating and the metal substrate is poor, which affects the service life and also has poor insulation performance.
The metal substrate is treated by electrochemical polishing, and then a Cr-Ce alloy coating and a Cr-Si-C insulating coating are sputtered and deposited on its surface. The mass fraction of the Ce element in the Cr-Ce alloy coating is controlled to ensure good bonding strength, and the insulation performance is improved by the Cr-Si-C insulating coating.
The bonding strength between the insulating coating and the metal substrate is improved, the insulation performance is enhanced, the service life of the insulating coating is extended, and the bonding strength is greater than 55N.
Smart Images

Figure CN120555953B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sputtering deposition insulating coating and a preparation method thereof, belonging to the technical field of insulating coatings. Background Art
[0002] In recent years, with the rapid development of electronic products, the demand for moving or stationary parts with electrical insulation requirements in this field has been increasing. And as the performance requirements for electronic products such as stability, service life and load bearing have become more and more stringent, people have become more and more stringent in the insulation performance, wear resistance and corrosion resistance of the insulating coating on the surface of electronic product parts. At present, the components of the insulating coating are mainly ceramic metal oxides or ceramic metal nitrides or chromium silicon carbide, etc., which have excellent physical and chemical properties, such as high breakdown field strength, high thermal conductivity, high resistivity, high chemical and thermal stability, etc., and can be used for insulation and dielectric isolation and packaging of electronic devices and integrated circuits. It is especially suitable for high-temperature and high-power devices to improve the reliability, accuracy and service life of electronic devices.
[0003] The preparation methods of the above-mentioned insulating coatings are mainly chemical vapor deposition, physical vapor deposition and magnetron sputtering. Chemical vapor deposition needs to be carried out in a high-temperature environment, which may affect the electronic device substrate. Physical vapor deposition can be carried out at low temperatures, but the deposition rate is slow. Magnetron sputtering technology has the advantages of high sputtering rate, good film-base bonding, and easy equipment operation. However, when using magnetron sputtering technology to prepare insulating coatings, the bonding strength between the insulating coating and the metal substrate is poor, which can easily cause the insulating coating to fall off, affecting the service life. Therefore, in order to improve the bonding strength between the insulating coating and the metal substrate, a bonding transition layer is usually set between the metal substrate and the insulating coating, or a metal layer is deposited on the metal substrate and then oxidized to a metal oxide insulating layer.
[0004] For example, Chinese patent document CN104789964A discloses a method for preparing a high-temperature insulating coating on a high-temperature alloy surface, comprising the following steps: 1) pre-treating the surface of a high-temperature alloy substrate; 2) depositing a Ti metal layer on the surface of the high-temperature alloy substrate; 3) further depositing a Cr metal layer on the Ti metal layer; 4) completely oxidizing the Cr metal layer on the surface of the high-temperature alloy substrate until the Ti metal layer is partially oxidized; 5) performing multiple pore sealing treatments on the oxidized coating surface using a high-temperature insulating material to fill the pores in the coating; 6) sputtering Cr2O3 on the surface coating to fill the remaining gaps in the surface coating; and 7) heat-treating the high-temperature alloy substrate to convert the Cr2O3 crystal form in the coating to α-Cr2O3. However, in this patent document, the oxidation of the Cr metal layer produces a porous structure, which requires filling with a high-temperature insulating material. However, the bonding between the filling material and the pores is poor, resulting in poor overall performance of the insulating coating.
[0005] Therefore, there is an urgent need to provide a method for preparing an insulating coating that has both good bonding strength with a metal substrate and excellent insulating properties. Summary of the Invention
[0006] The purpose of the present invention is to provide a sputtering deposited insulating coating and a preparation method thereof, so as to solve the problem that the bonding strength between the insulating coating and the metal substrate and the insulating performance of the insulating coating cannot be achieved simultaneously when the insulating coating is currently prepared on a metal substrate.
[0007] The technical solution of the method for preparing the sputtering deposition insulating coating of the present invention is as follows:
[0008] A method for preparing a sputter-deposited insulating coating comprises the following steps: cleaning and electrochemically polishing a metal substrate to obtain a pretreated metal substrate; then sputter-depositing a Cr-Ce alloy coating on the surface of the pretreated metal substrate, wherein the Cr-Ce alloy coating has a thickness of 2 to 4 μm, the mass fraction of the Ce element in the Cr-Ce alloy coating is 4.5 to 5.8%, and the balance is Cr; and finally sputter-depositing a Cr-Si-C insulating coating on the surface of the Cr-Ce alloy coating. The electrolytic polishing solution during the electrochemical polishing comprises water, thiourea, modified phosphoric acid, and 2-(diethanolamino)ethanesulfonic acid, wherein the mass fraction of the thiourea is 1 to 3%, the mass fraction of the modified phosphoric acid is 10 to 15%, and the mass fraction of the 2-(diethanolamino)ethanesulfonic acid is 20 to 35%. The structure of the modified phosphoric acid is as follows:
[0009] .
[0010] Preferably, during electrochemical polishing, the temperature of the electrochemical polishing solution is 40-45°C, and the current density is 0.3-0.5 A / cm 2 The electrochemical polishing time is 5 to 7 minutes.
[0011] Preferably, the metal substrate is a stainless steel substrate.
[0012] Preferably, the stainless steel substrate is made of 316 stainless steel.
[0013] Preferably, when sputtering and depositing the Cr—Ce alloy coating on the surface of the pretreated metal substrate, a Cr target and a Ce target are used as target materials, and the pressure during sputtering deposition is 0.1-0.3 Pa.
[0014] Preferably, the sputtering power of the Cr target is 70-80W, and the sputtering power of the Ce target is 8-15W.
[0015] Preferably, the thickness of the Cr-Si-C insulating coating is 1.2-2.5 μm, the mass fraction of carbon element in the Cr-Si-C insulating coating is 94-96%, and the molar ratio of Cr element to Si element is 1:1.
[0016] Preferably, the modified phosphoric acid is prepared by reacting 3-dimethylaminoallyl phosphoric acid and piperazine.
[0017] Preferably, the reaction temperature of 3-dimethylaminoallyl phosphoric acid and piperazine is 50-60° C., and the reaction time is 5-7 h; the molar ratio of 3-dimethylaminoallyl phosphoric acid to piperazine is 2.2-2.5:1.
[0018] The technical solution of the sputtering deposition insulating coating of the present invention is as follows:
[0019] A sputtering deposited insulating coating is prepared by the method for preparing the sputtering deposited insulating coating as described above.
[0020] Compared to the prior art, the present invention has the following beneficial technical effects: By electrochemically polishing a metal substrate to obtain a smooth, flat, and roughened pretreated metal substrate, the present invention then sputter-deposits a Cr-Ce alloy coating on the surface of the pretreated metal substrate. Controlling the mass fraction of Ce in the Cr-Ce alloy coating ensures a high bonding strength between the Cr-Ce alloy coating and the pretreated metal substrate, and provides good adhesion to the Cr-Si-C insulating coating, thereby improving the service life of the insulating coating. The sputter-deposited insulating coating prepared by the present invention exhibits excellent insulating properties, and the bonding strength between the insulating coating and the stainless steel substrate is greater than 55N. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the H NMR spectrum of the modified phosphoric acid prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The following examples are intended to further illustrate the present invention, but are not intended to limit the scope of protection of the present invention.
[0023] Example 1
[0024] The method for preparing the sputtering-deposited insulating coating of this embodiment includes the following steps:
[0025] (1) The stainless steel metal substrate is cleaned and electrochemically polished to obtain a pretreated metal substrate; water and ethanol are used as cleaning agents in sequence during cleaning; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, modified phosphoric acid and 2-(diethanolamino)ethanesulfonic acid, with the mass fraction of thiourea being 1%, the mass fraction of modified phosphoric acid being 10%, and the mass fraction of 2-(diethanolamino)ethanesulfonic acid being 20%; during electrochemical polishing, the temperature of the electrochemical polishing solution is 40°C, and the current density is 0.3A / cm 2, the electrochemical polishing time is 5 minutes. Among them, the stainless steel substrate is made of stainless steel 316. The preparation method of modified phosphoric acid is as follows: double-bond functionalized phosphoric acid and acetonitrile are added to a reactor and stirred evenly to obtain a double-bond functionalized phosphoric acid solution with a mass fraction of 12%; then piperazine is added to the reactor, heated to 50°C, stirred for 5 hours, and acetonitrile is removed by vacuum distillation to obtain a concentrated solution. The condensate is purified by column chromatography (the eluent used for purification is composed of methanol, ethyl acetate and petroleum ether in a volume ratio of 2:1:6) to obtain modified phosphoric acid (the nuclear magnetic hydrogen spectrum of the modified phosphoric acid is shown as follows). Figure 1 ). The double-bond functionalized phosphoric acid is 3-dimethylaminoallyl phosphoric acid, the molar ratio of the double-bond functionalized phosphoric acid to piperazine is 2.2:1, and the structure of the modified phosphoric acid is as follows:
[0026] .
[0027] (2) Place the pretreated metal substrate in a magnetron sputtering device, use Cr target and Ce target as target materials, and evacuate the vacuum chamber to 6×10 -3 Pa, and then argon gas is introduced into the vacuum chamber, and the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.1 Pa. The sputtering power of the Cr target is set to 70 W, and the sputtering power of the Ce target is set to 8 W. A Cr-Ce alloy coating is sputtered to form the surface of the stainless steel metal substrate after electrochemical polishing. The thickness of the Cr-Ce alloy coating is 2 μm, and the mass fraction of the Ce element in the Cr-Ce alloy coating is 4.5%, and the balance is Cr element.
[0028] (3) The stainless steel substrate with Cr-Ce alloy coating deposited on its surface was placed in a magnetron sputtering device, with CrSi target as target material, and the vacuum chamber was first evacuated to 1×10 -5 Pa, and then argon and acetylene are introduced into the vacuum chamber, the working pressure of the vacuum chamber is controlled to 0.4 Pa, the sputtering power of the CrSi target is set to 280 W, and a Cr-Si-C insulating coating with a thickness of 1.2 μm is sputtered on the surface of the Cr-Ce alloy coating. The mass fraction of carbon element in the Cr-Si-C insulating coating is 94%, and the molar ratio of Cr element to Si element is 1:1.
[0029] Example 2
[0030] The method for preparing the sputtering-deposited insulating coating of this embodiment includes the following steps:
[0031] (1) The stainless steel metal substrate is cleaned and electrochemically polished to obtain a pretreated metal substrate; water and ethanol are used as cleaning agents in sequence during cleaning; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, modified phosphoric acid and 2-(diethanolamino)ethanesulfonic acid, with the mass fraction of thiourea being 2%, the mass fraction of modified phosphoric acid being 12%, and the mass fraction of 2-(diethanolamino)ethanesulfonic acid being 30%; during electrochemical polishing, the temperature of the electrochemical polishing solution is 42°C and the current density is 0.4A / cm 2 The electrochemical polishing time is 6 minutes. The stainless steel substrate is made of 316 stainless steel. The modified phosphoric acid is prepared as follows: double-bond functionalized phosphoric acid and acetonitrile are added to a reactor and stirred evenly to obtain a 14% by mass double-bond functionalized phosphoric acid solution. Piperazine is then added to the reactor, heated to 55°C, and stirred for 6 hours. The acetonitrile is removed by vacuum distillation to obtain a concentrated solution. The condensate is purified by column chromatography (the eluent used for purification is composed of methanol, ethyl acetate, and petroleum ether in a volume ratio of 2:1:6) to obtain the modified phosphoric acid. The double-bond functionalized phosphoric acid is 3-dimethylaminoallyl phosphoric acid, and the molar ratio of double-bond functionalized phosphoric acid to piperazine is 2.3:1. The structure of the modified phosphoric acid is as follows:
[0032] .
[0033] (2) Place the pretreated metal substrate in a magnetron sputtering device, use Cr target and Ce target as target materials, and evacuate the vacuum chamber to 6×10 -3 Pa, and then argon gas is introduced into the vacuum chamber, and the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.1 Pa. The sputtering power of the Cr target is set to 70 W, and the sputtering power of the Ce target is set to 11 W. A Cr-Ce alloy coating is sputtered on the surface of the stainless steel metal substrate after electrochemical polishing. The thickness of the Cr-Ce alloy coating is 3 μm, and the mass fraction of the Ce element in the Cr-Ce alloy coating is 5.1%, and the balance is Cr element.
[0034] (3) The stainless steel substrate with Cr-Ce alloy coating deposited on its surface was placed in a magnetron sputtering device, with CrSi target as target material, and the vacuum chamber was first evacuated to 1×10 -5 Pa, and then argon and acetylene are introduced into the vacuum chamber, the working pressure of the vacuum chamber is controlled to 0.4 Pa, the sputtering power of the CrSi target is set to 280 W, and a Cr-Si-C insulating coating with a thickness of 1.9 μm is sputtered on the surface of the Cr-Ce alloy coating. The mass fraction of carbon element in the Cr-Si-C insulating coating is 95%, and the molar ratio of Cr element to Si element is 1:1.
[0035] Example 3
[0036] The method for preparing the sputtering-deposited insulating coating of this embodiment includes the following steps:
[0037] (1) The stainless steel metal substrate is cleaned and electrochemically polished to obtain a pretreated metal substrate; water and ethanol are used as cleaning agents in sequence during cleaning; the electrolytic polishing solution during electrochemical polishing consists of water, thiourea, modified phosphoric acid and 2-(diethanolamino)ethanesulfonic acid, with the mass fraction of thiourea being 3%, the mass fraction of modified phosphoric acid being 15%, and the mass fraction of 2-(diethanolamino)ethanesulfonic acid being 35%; during electrochemical polishing, the temperature of the electrochemical polishing solution is 45°C, and the current density is 0.5A / cm 2 The electrochemical polishing time was 7 minutes. The stainless steel substrate was made of 316 stainless steel. The modified phosphoric acid was prepared as follows: double-bond functionalized phosphoric acid and acetonitrile were added to a reactor and stirred evenly to obtain a 16% by mass double-bond functionalized phosphoric acid solution. Piperazine was then added to the reactor, heated to 60°C, and stirred for 7 hours. The acetonitrile was removed by vacuum distillation to obtain a concentrated solution. The condensate was purified by column chromatography (the eluent used for purification consisted of methanol, ethyl acetate, and petroleum ether in a volume ratio of 2:1:6) to obtain the modified phosphoric acid. The double-bond functionalized phosphoric acid was 3-dimethylaminoallyl phosphoric acid, and the molar ratio of double-bond functionalized phosphoric acid to piperazine was 2.5:1. The structure of the modified phosphoric acid is as follows:
[0038] .
[0039] (2) Place the pretreated metal substrate in a magnetron sputtering device, use Cr target and Ce target as target materials, and evacuate the vacuum chamber to 6×10 -3 Pa, and then argon gas is introduced into the vacuum chamber, and the introduction rate and time of argon gas are controlled to make the working pressure of the vacuum chamber 0.1 Pa. The sputtering power of the Cr target is set to 70 W, and the sputtering power of the Ce target is set to 15 W. A Cr-Ce alloy coating is sputtered on the surface of the stainless steel metal substrate after electrochemical polishing. The thickness of the Cr-Ce alloy coating is 4 μm, and the mass fraction of the Ce element in the Cr-Ce alloy coating is 5.8%, and the balance is Cr element.
[0040] (3) The stainless steel substrate with Cr-Ce alloy coating deposited on its surface was placed in a magnetron sputtering device, with CrSi target as target material, and the vacuum chamber was first evacuated to 1×10 -5 Pa, and then argon and acetylene are introduced into the vacuum chamber, the working pressure of the vacuum chamber is controlled to 0.4 Pa, the sputtering power of the CrSi target is set to 280 W, and a Cr-Si-C insulating coating with a thickness of 2.5 μm is sputtered on the surface of the Cr-Ce alloy coating. The mass fraction of carbon element in the Cr-Si-C insulating coating is 96%, and the molar ratio of Cr element to Si element is 1:1.
[0041] Comparative Example 1
[0042] The difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that the electrolytic polishing liquid in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example consists of water, modified phosphoric acid and 2-(diethanolamino)ethanesulfonic acid, the mass fraction of the modified phosphoric acid is 10.3%, and the mass fraction of 2-(diethanolamino)ethanesulfonic acid is 20.7%. The modified phosphoric acid is the same as the modified phosphoric acid in Example 1.
[0043] Comparative Example 2
[0044] The only difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that the electrolytic polishing liquid in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example consists of water, thiourea and 2-(diethanolamino)ethanesulfonic acid, the mass fraction of thiourea is 1.5%, the mass fraction of 2-(diethanolamino)ethanesulfonic acid is 29.5%, and the modified phosphoric acid is the same as the modified phosphoric acid in Example 1.
[0045] Comparative Example 3
[0046] The only difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that the electrolytic polishing liquid in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example consists of water, thiourea and modified phosphoric acid, the mass fraction of thiourea is 3%, the mass fraction of the modified phosphoric acid is 28%, and the modified phosphoric acid is the same as the modified phosphoric acid in Example 1.
[0047] Comparative Example 4
[0048] The difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that in the electrolytic polishing liquid in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example, 2-(diethanolamino)ethanesulfonic acid is replaced by aminosulfonic acid.
[0049] Comparative Example 5
[0050] The only difference between the method for preparing the sputtering deposited insulating coating of this comparative example and the method for preparing the sputtering deposited insulating coating of Example 1 is that thiourea is replaced by urea in the electrolytic polishing liquid in step (1) of the method for preparing the sputtering deposited insulating coating of this comparative example.
[0051] Comparative Example 6
[0052] The difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that the preparation method of the modified phosphoric acid in the electrolytic polishing solution in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example is as follows: double-bond functionalized phosphoric acid and acetonitrile are added to a reactor and stirred evenly to obtain a double-bond functionalized phosphoric acid solution with a mass fraction of 12%; then piperazine is added to the reactor, heated to 50°C, stirred for reaction for 5 hours, and the acetonitrile is removed by vacuum distillation to obtain a concentrated solution, and the condensate is purified by column chromatography (the eluent used for purification is composed of methanol, ethyl acetate and petroleum ether in a volume ratio of 2:1:6) to obtain modified phosphoric acid. Wherein, the double-bond functionalized phosphoric acid is allylphosphonic acid, and the molar ratio of double-bond functionalized phosphoric acid to piperazine is 2.2:1.
[0053] Comparative Example 7
[0054] The difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that the preparation method of the modified phosphoric acid in the electrolytic polishing solution in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example is as follows: double-bond functionalized phosphoric acid and acetonitrile are added to a reactor and stirred evenly to obtain a double-bond functionalized phosphoric acid solution with a mass fraction of 12%; then dimethylethylenediamine is added to the reactor, heated to 50°C, stirred for reaction for 5 hours, and acetonitrile is removed by vacuum distillation to obtain a concentrated solution, and the condensate is purified by column chromatography (the eluent used for purification is composed of methanol, ethyl acetate and petroleum ether in a volume ratio of 2:1:6) to obtain modified phosphoric acid. Wherein, the double-bond functionalized phosphoric acid is 3-dimethylaminoallyl phosphoric acid, and the molar ratio of the double-bond functionalized phosphoric acid to dimethylethylenediamine is 2.2:1.
[0055] Comparative Example 8
[0056] The difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that the preparation method of the modified phosphoric acid in the electrolytic polishing solution in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example is as follows: double-bond functionalized phosphoric acid and acetonitrile are added to a reactor and stirred evenly to obtain a double-bond functionalized phosphoric acid solution with a mass fraction of 12%; then N1,N4-dimethyl-1,4-cyclohexanediamine is added to the reactor, heated to 50°C, stirred for reaction for 5 hours, and acetonitrile is removed by vacuum distillation to obtain a concentrated solution, and the condensate is purified by column chromatography (the eluent used for purification is composed of methanol, ethyl acetate and petroleum ether in a volume ratio of 2:1:6) to obtain modified phosphoric acid. Wherein, the double-bond functionalized phosphoric acid is 3-dimethylaminoallyl phosphoric acid, and the molar ratio of double-bond functionalized phosphoric acid to N1,N4-dimethyl-1,4-cyclohexanediamine is 2.2:1.
[0057] Comparative Example 9
[0058] The difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that in step (1) of the preparation method of the sputtering deposited insulating coating of this comparative example, the modified phosphoric acid in the electrolytic polishing solution is replaced by phosphoric acid.
[0059] Comparative Example 10
[0060] The only difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that in step (2) of the preparation method of the sputtering deposited insulating coating of this comparative example, the mass fraction of the Ce element in the Cr-Ce alloy coating is adjusted from 4.5% to 3.8% by adjusting the sputtering parameters, and the remainder is the Cr element.
[0061] Comparative Example 11
[0062] The only difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that in step (2) of the preparation method of the sputtering deposited insulating coating of this comparative example, the mass fraction of the Ce element in the Cr-Ce alloy coating is adjusted from 4.5% to 6.4% by adjusting the sputtering parameters, and the remainder is the Cr element.
[0063] Comparative Example 12
[0064] The only difference between the preparation method of the sputtering deposited insulating coating of this comparative example and the preparation method of the sputtering deposited insulating coating of Example 1 is that in step (2) of the preparation method of the sputtering deposited insulating coating of this comparative example, the mass fraction of the Ce element in the Cr-Ce alloy coating is adjusted from 4.5% to 0% by adjusting the sputtering parameters, and the mass fraction of the Cr element is 100%.
[0065] Experimental Example 1
[0066] In order to investigate the smoothness of the surface of the stainless steel metal substrate after electrochemical polishing and the bonding strength of the Cr-Ce alloy coating on the pretreated metal substrate in each embodiment and comparative example, the appearance of the stainless steel metal substrate after electrochemical polishing was observed, and the surface roughness was measured using a surface roughness meter. The results are shown in Table 1. The adhesion of the Cr-Ce alloy coating on the pretreated metal substrate surface was then tested using a WS-2005 coating adhesion scratch tester. The test was performed at a loading speed of 50 N / min and a scratch speed of 4 mm / min. Three parallel samples were tested, and the average of the test results of the three parallel samples was used as the final test result. The test results are shown in Table 1.
[0067] Table 1 Surface appearance of stainless steel metal substrate after electrochemical polishing and adhesion of Cr-Ce alloy coating in various examples and comparative examples
[0068]
[0069] It can be seen from the test results in Table 1 that in Examples 1-3 of the present invention, a suitable electrochemical polishing process is adopted to corrode the surface of the stainless steel substrate to form a certain rough surface. When the Cr-Ce alloy coating is sputtered and deposited on the surface of the electrochemically polished stainless steel substrate, the gap between the Cr-Ce alloy coating and the surface of the stainless steel substrate is sufficiently small, and there is a large contact area between the two, thereby ensuring that the Cr-Ce alloy coating has good bonding strength on the surface of the stainless steel substrate.
[0070] It can be seen from Example 1 and Comparative Examples 1, 3, 6 and 9 that when the electrolyte used for electrochemical polishing is adjusted, the roughness of the stainless steel substrate surface increases, resulting in a larger gap between the Cr-Ce alloy coating and the stainless steel substrate surface, which is not conducive to improving the bonding strength between the two.
[0071] It can be seen from Example 1, Comparative Example 2, and Comparative Examples 7-8 that when the electrolyte used for electrochemical polishing is adjusted, although the roughness of the stainless steel substrate surface is reduced, its surface is too smooth, which is not conducive to increasing the contact area between the Cr-Ce alloy coating and the stainless steel substrate surface, resulting in a decrease in the bonding strength between the two.
[0072] It can be seen from Example 1 and Comparative Examples 4-5 that by replacing thiourea and 2-(diethanolamino)ethanesulfonic acid in the electrolytic polishing solution, although the roughness of the stainless steel substrate surface after electrochemical polishing is close to that of Examples 1-3, the bonding strength between the prepared Cr-Ce alloy coating and the stainless steel substrate surface is poor. This shows that in addition to the roughness of the stainless steel substrate surface, other physical and chemical properties of the stainless steel substrate surface (for example, surface chemical composition and chemical group type, etc.) also have a significant effect on the bonding strength between the Cr-Ce alloy coating and the stainless steel substrate surface.
[0073] As shown in Example 1 and Comparative Examples 9-10, when the mass fraction of Ce in the Cr-Ce alloy coating is adjusted, the bonding strength between the Cr-Ce alloy coating and the stainless steel substrate surface also decreases, indicating that the mass fraction of Ce in the Cr-Ce alloy coating also has a significant effect on the bonding strength between the Cr-Ce alloy coating and the stainless steel substrate surface. This may be because Ce can adjust the flexibility and strength of the Cr coating. When the mass fraction of Ce is too high or too low, the strength and flexibility of the Cr-Ce alloy coating cannot match that of the stainless steel substrate, resulting in excessive internal stress in the coating and reduced adhesion.
[0074] Experimental Example 2
[0075] To evaluate the bonding strength between the insulating coatings and the Cr-Ce alloy coatings prepared in Examples 1-3 and Comparative Examples 10-12, as well as the insulating properties of the insulating coatings, the insulating coatings' adhesion F1 was tested using a WS-2002 coating adhesion scratch tester at a loading speed of 50 N / min and a scratching speed of 4 mm / min. Three parallel samples were tested, and the average of the three parallel test results was used as the final test result. The test results are shown in Table 2. The stainless steel sheets with the sputtered insulating coatings were then placed in boiling water for 1 hour, and excess water was wiped off with a dust-free cloth. The insulating coatings' adhesion F2 was then tested using the WS-2002 coating adhesion scratch tester according to the aforementioned method. The test results are shown in Table 2. Finally, a multimeter was used to measure the resistance R1 between any two points on the surface of the insulating coating, and a megohmmeter was used to measure the resistance R2 between two points on the surface of the insulating coating with a distance of 10 mm × 10 mm at a voltage of 500 V. The test results are shown in Table 2. Three parallel samples were used for testing, and the average value of the test results of the three parallel samples was taken as the final test result.
[0076] Table 2 Bonding strength between the insulating coatings and the Cr-Ce alloy coatings prepared in Examples 1-3 and Comparative Examples 10-12 and the insulating properties of the insulating coatings
[0077]
[0078] As can be seen from the test results in Table 2, the sputtered deposited insulating coating prepared by the present invention has good bonding strength on the stainless steel substrate, which can effectively improve the service life and service life of the insulating coating, and the sputtered deposited insulating coating prepared by the present invention exhibits good insulating properties. However, the bonding strength of the insulating coating prepared in Comparative Examples 10-12 is poor, indicating that the mass fraction of the Ce element in the Cr-Ce alloy coating has a significant effect on the adhesion of the Cr-Si-C insulating coating. In addition, the insulating properties of the insulating coating prepared in Comparative Examples 10-12 also decreased, which may be because the mass fraction of the Ce element in the Cr-Ce alloy coating affects the microstructure of the sputtered deposited alumina bonding coating, thereby affecting the insulation resistance of the Cr-Si-C insulating coating.
Claims
1. A method for preparing a sputtering deposited insulating coating, characterized in that: The following steps are involved: The metal substrate is cleaned and electrochemically polished to obtain a pretreated metal substrate; a Cr-Ce alloy coating is then sputtered on the surface of the pretreated metal substrate, wherein the thickness of the Cr-Ce alloy coating is 2-4 μm, the mass fraction of the Ce element in the Cr-Ce alloy coating is 4.5-5.8%, and the balance is Cr; finally, a Cr-Si-C insulating coating is sputtered on the surface of the Cr-Ce alloy coating; the electrolytic polishing solution during the electrochemical polishing comprises water, thiourea, modified phosphoric acid, and 2-(diethanolamino)ethanesulfonic acid, wherein the mass fraction of thiourea is 1-3%, the mass fraction of the modified phosphoric acid is 10-15%, and the mass fraction of the 2-(diethanolamino)ethanesulfonic acid is 20-35%; the structure of the modified phosphoric acid is as follows: 。 2. The method for preparing a sputtering-deposited insulating coating according to claim 1, wherein: During the electrochemical polishing, the temperature of the electrochemical polishing solution is 40-45°C, and the current density is 0.3-0.5A / cm 2 The electrochemical polishing time is 5 to 7 minutes.
3. The method for preparing a sputtering-deposited insulating coating according to claim 1, wherein: The metal substrate is a stainless steel substrate.
4. The method for preparing a sputtering-deposited insulating coating according to claim 3, wherein: The stainless steel substrate is made of 316 stainless steel.
5. The method for preparing a sputtering-deposited insulating coating according to claim 1, wherein: When sputtering and depositing the Cr-Ce alloy coating on the surface of the pretreated metal substrate, a Cr target and a Ce target are used as target materials, and the pressure during sputtering deposition is 0.1~0.3Pa.
6. The method for preparing a sputtering-deposited insulating coating according to claim 5, wherein: The sputtering power of the Cr target is 70-80W, and the sputtering power of the Ce target is 8-15W.
7. The method for preparing a sputtering-deposited insulating coating according to claim 1, wherein: The thickness of the Cr-Si-C insulating coating is 1.2-2.5 μm, the mass fraction of carbon element in the Cr-Si-C insulating coating is 94-96%, and the molar ratio of Cr element to Si element is 1:
1.
8. The method for preparing a sputtering-deposited insulating coating according to any one of claims 1 to 7, wherein: The modified phosphoric acid is prepared by reacting 3-dimethylamino allyl phosphoric acid and piperazine.
9. The method for preparing a sputtering-deposited insulating coating according to claim 8, wherein: The reaction temperature of 3-dimethylaminoallyl phosphoric acid and piperazine is 50-60° C., and the reaction time is 5-7 hours. The molar ratio of 3-dimethylaminoallyl phosphoric acid to piperazine is 2.2-2.5:
1.
10. A sputter-deposited insulating coating prepared by the method for preparing a sputter-deposited insulating coating according to claim 1.
Citation Information
Patent Citations
Preparation method of high-temperature insulation coating on surface of high-temperature alloy
CN104789964A
High-temperature-resisting and corrosion-resisting multilayer composite film and preparation method
CN111254395A
CrSiC composite coating with high-temperature oxidation resistance and structural thermal stability as well as preparation method and application of CrSiC composite coating
CN117604473A